Reasserting curriculum design through virtual learning environments: The case of MAPE - Sousa, Francisco (2016)
MAPE is a curricular model for virtual learning at the University of the Azores, Portugal. After being used for teaching Curriculum Theory and Development through e-learning and b-learning, this model has been, in theacademic year 2014/15, extended to other courses. Besides describing the model and explaining its evolution, this paper reports a study of its implementation, for the first time, by more than one instructor. Accordingly, the main objective of the study is to test the MAPE model on a multi-course level. In this specific case, the model has been implemented in eight courses from the specialization program in e-learning. A more theoretical objective is also pursued: to explore the development of a curricular model for virtual learning environments as an opportunity to discuss the role of curriculum design in contemporary Curriculum Studies. Assuming that curriculum design can be defined as the arrangement of the elements of a curriculum, including educational materials, and that virtual learning environments are especially rich in resources that can be arranged in multiple ways, it is important to discuss the creative potential of this relationship between curriculum design and e-learning.The methodology that has been used to study the development of MAPE is design research, which aims at providing design principles for making a product, assuming that such approach is applicable to different kinds of products, including artifacts, activities, services, policies, environments, educational materials, virtual learning environments, and curricula. More specifically, the study of MAPE can be considered an instance of the application of design research to e-learning, inasmuch as it aims at generating guidelines for developing virtual learning environments. It can also be can be viewed as an instance of curriculum design research – a variation of educational design research whereby one studies the design of either a curriculum or a particular aspect of a curriculum. Design research is usually based on the construction and evaluation of a succession of prototypes of the product, which, besides aiming at its improvement, is expected to generate design principles that can be adopted in a wide range of contexts. Prototypes 1 and 2 of MAPE had been evaluated at a very small scale. In 2014/15, through the adoption of Prototype 3 in several courses from a specialization program, MAPE is being used, for the first time, by instructors who did not participate in the first stages of its design. This paper is focused on the evaluation of the model in this wider context. The main evaluation tool being used at this stage is a student questionnaire.Considering that this paper is being submitted before the end of the second semester, it presents results from the first semester only. Such results reveal a very high level of student satisfaction with the model in terms of its practicality and effectiveness. Considering that the results of the previous moment of evaluation had not been so satisfactory, the paper discusses possible reasons for such differences in student satisfaction and their implications in terms of the consolidation of design principles.